2010
DOI: 10.1063/1.3358117
|View full text |Cite
|
Sign up to set email alerts
|

Electric field-modulated amplified spontaneous emission in waveguides based on poly [2-methoxy-5-(2′-ethylhexyloxy)-1, 4-phenylene vinylene]

Abstract: We report amplified spontaneous emission (ASE) in an optically pumped symmetric thin film waveguide based on poly [2-methoxy-5-(2′-ethylhexyloxy)-1, 4-phenylene vinylene] (MEH-PPV) and electric-field modulation of the ASE in the MEH-PPV thin film. The electric-field quenching of the ASE at 620 nm and the spontaneous emission (SE) at 580 nm was observed, which increased with the electric field. The ASE intensity was more effectively quenched than the SE intensity as the field increased. The field dependence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…where A is a free fit parameter, l the effective mass, h the Planck constant, e the unit charge, and E b the exciton binding energy. From the emission intensity measured in the presence and in the absence of electric field [I(F) and I(0), respectively], the quenching factor Q is introduced, which is proportional to ionization of excitons and tunneling probability, using 21,22,31,32…”
Section: Nh 3 Pbimentioning
confidence: 99%
“…where A is a free fit parameter, l the effective mass, h the Planck constant, e the unit charge, and E b the exciton binding energy. From the emission intensity measured in the presence and in the absence of electric field [I(F) and I(0), respectively], the quenching factor Q is introduced, which is proportional to ionization of excitons and tunneling probability, using 21,22,31,32…”
Section: Nh 3 Pbimentioning
confidence: 99%
“…In order to answer this question, Zhang et al utilized the strong electric field, and observed that, when the applied electric field approaches and exceed a threshold, ASE in poly[2-methoxy-5-(2 -ethylhexyloxy)-p-phenylene vinylene (MEH-PPV) thin film is weakened accordingly, and even quenched, similar to the electric field-induced quenching of luminescence of PLEDs. 19 Just by analogy between polymer ASE and polymer light-emitting diodes, this phenomenon is attributed to the previously-mentioned dissociation of excitons in a PLEDs thin film. 19 We recognize that the electronic structure of the exciton is just an electron-hole pair.…”
mentioning
confidence: 97%
“…19 Just by analogy between polymer ASE and polymer light-emitting diodes, this phenomenon is attributed to the previously-mentioned dissociation of excitons in a PLEDs thin film. 19 We recognize that the electronic structure of the exciton is just an electron-hole pair. Different from this particular structure, ASE or laser action is triggered by electron population inversion.…”
mentioning
confidence: 99%
“…However, the processing of small organic molecules for device fabrication is more complex (and expensive) than the processing of conjugated polymers. Conjugated polymers have attracted considerable interest for applications in the fields of light-emitting diodes, flat panel displays, and solar cells, because they are compatible with inorganic semiconductors, have high photoluminescence quantum efficiencies, and are inexpensive to fabricate [12][13][14][15][16][17]. Additionally, most conjugated polymers are transparent in the THz range, and they have not yet been used in THz modulators and switches.…”
mentioning
confidence: 99%
“…The generated THz pulses had a normal angle of incidence to the polymer/inorganic hybrid structures, while the external CW semiconductor laser beam had an oblique angle of incidence. The external CW laser beam has a wavelength of 450 nm, which is strongly absorbed by silicon, although it locates in the absorption band of MEH-PPV [15,16,18]. The transmitted THz waveform was detected using a ZnTe crystal, with an electro-optic sampling technique [19].…”
mentioning
confidence: 99%